Gigantic retroperitoneal leiomyosarcoma – case report - Snarska, Jadwiga; Hady, Hady; Kamiński, Fabian; Szajda, Sławomir Dariusz; Werel, Dorota; Zimnoch, Lech; Siemiątkowski, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2007)
Retroperitoneal leiomyosarcomas are very rare malignant neoplasms. They are built up of smooth muscle cells. They can be found beyond the retroperitoneal space in the uterus, the stomach, the intestines, the blood vessel walls and the skin. This type of tumour grows slowly and gives no characteristic clinical symptoms. This results in late diagnosis, when they grow to a huge size. Retroperitoneal leiomyosarcomas are most frequently described in the literature in the fifth or sixth decade of life. There are no biochemical markers which could suggest the development of leiomyosarcoma. The basic diagnostic examination includes: ultrasound and computer tomography of the abdomen. The fundamental treatment of retroperitoneal leiomyosarcomas consists in aggressive surgical treatment – complete tumour resection. Large size of the tumour can make it difficult to perform radical surgery. In the case presented in this report, our team managed to remove a retroperitoneal leiomyosarcoma completely despite its huge mass and size (300x200 mm). Data from the literature indicate that a complete resection of the tumour is the most significant prognostic factor in the case of patients with retroperitoneal leiomyosarcoma. The efficacy of radiotherapy and chemotherapy has not been proved. The other unfavourable prognostic factor in the course of sarcomas is the age of the patient, below 50 years old. The patient presented in the report is a 31-year-old woman, which is associated with a worse prognosis. According to some authors, the size of the tumour is not significant for the fast recurrence of the disease, whereas others state that it is. The case was presented because of such a huge leiomyosarcoma being rarely found in the retroperitoneal space, the age of the patient and the asymptomatic course of the disease.